EVALUATION OF ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICALS ANALYSIS OF WHOLE PLANT EXTRACT OF VINCA ROSEA - ANGELIN JEBAMALAR JAYARAJ; JOTHI UCHIMAHALI; THIYAGARAJAN GNANASUNDARAM; SIVAKUMAR THIRUMAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of this research work was to find out the antibacterial activity and phytochemical analysis of whole plant extracts (shoot, flower, and root) of Vinca rosea. Methods: In recent work, phytochemicals were extracted from various parts of the plants using various solvents ethyl acetate (ETOAC), ethanol (ETOH), and dimethyl sulfoxide (DMSO). These phytochemicals contain alkaloids, terpenoids, tannins, flavonoids, aminoacids, saponins, aromatic acids, phenolic compounds, triterpenoids, xantho proteins, PHILOBATININS, carbohydrate, reducing sugar, and proteins; and they were separated by the standard methods. Moreover, antimicrobial activities of methanolic separation were determined by a different species of bacteria and fungi. Agar well-diffusion method was used for the antimicrobial activity, and also analyzed the zone of inhibition. Results: The evaluation of phytochemical screening of extracts indicated the existence of alkaloids, terpenoids, tannins, flavonoids, aminoacids, saponins, aromatic acids, phenolic compounds, triterpenoids, xantho proteins, philobatinins, carbohydrate, reducing sugar, and proteins. All the tested bacteria and fungi were controlled efficiently, and the activities of the shoot extracts were better compared to flower and root extracts. ETOH extract of the shoot exhibited highest antifungal activity against Candida albicans, (17.34 mm), followed by Candida krusei (16.12 mm), Aspergillus niger (15.76), Mucor sp. (14.67 mm), and Rhizopus oryzae (13.46 mm), ETOH extract of the shoot exhibited highest antibacterial activity), when compared to flower and root extracts against Staphylococcus aureus (12.77 mm), followed by Pseudomonas aeruginosa (11.67 mm), Salmonella abony (10.23 mm), Escherichia coli (9.65 mm), Micrococcus luteus (8.95 mm. V. rosea shoot extracts highlighted effective antifungal activities compared with flower and root extracts against all the tested bacteria. Conclusion: Current studies have shown that the V. rosea plant contains significant antimicrobial activities in the ETOH extracts. The strong antifungal and antibacterial activities of V. rosea are owing to the presence of saponin, tannins, and flavonoids present in.